Thyroid disorders and the incidence of type 2 diabetes: insights from a 10-year cohort study in Germany - Theresia Sarabhai; Karel Kostev (Endocrine Connections)
Background: Thyroid dysfunctions, such as hypothyroidism and hyperthyroidism, are known to influence metabolism, but their long-term impact on the development of type 2 diabetes (T2D) mellitus in humans remains elusive. Thus, this study aimed to assess the cumulative incidence and association between thyroid disorders and T2D development. Methods: We conducted a retrospective cohort study using data from the Disease Analyzer database (IQVIA™, USA) from 2005 to 2022. The study included 158,674 patients with thyroid disorders and an equal number of matched patients without thyroid disorders. Propensity score matching was performed to balance age, sex and codiagnoses between the cohorts. Kaplan–Meier curves and Cox regression models were used to assess the cumulative incidence and hazard ratios (HRs) for new-onset T2D. Results: After a 10-year follow-up period, the cumulative incidence of T2D was higher in patients with thyroid disorders compared to the non-thyroid disorder cohort (P < 0.001). The HRs for T2D were 1.34 (95% CI: 1.28–1.39) for hypothyroidism and 1.30 (95% CI: 1.21–1.39) for hyperthyroidism. The strongest associations were observed in younger age groups for both hypothyroidism and hyperthyroidism. Conclusion: Thyroid disorders, including hypothyroidism and hyperthyroidism, are associated with an increased incidence of new-onset T2D. These findings suggest the need for proactive screening and management of glucose metabolism in patients with thyroid dysfunctions, particularly in younger individuals, independent of metabolic risk factors.